2005
DOI: 10.1097/01.ccm.0000171839.65687.f5
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for critically ill children with traumatic brain injuries: A longitudinal analysis*

Abstract: More aggressive management of pediatric traumatic brain injury appears to have contributed to reduced mortality rates over time and saved thousands of lives. Additional lives could be saved if mortality rates could be equalized between insured and uninsured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 37 publications
3
32
1
1
Order By: Relevance
“…That the study group so defined was "severe" is supported by the overall mortality rate of 24%, which is comparable to mortality rates for severe TBI among children defined by GCS or AIS scores in contemporary case series and prospective trials. 2,9,11,17,24,25,34,35,39,40,43,44,46,47 Nevertheless, the rate of neurosurgical procedures in the current study group (46.8%) was unexpectedly low. Even among admissions lasting 2 days or longer and ending in death, the rate of neurosurgical procedures was only 67.3%.…”
Section: The Missing Icp Monitorsmentioning
confidence: 76%
See 3 more Smart Citations
“…That the study group so defined was "severe" is supported by the overall mortality rate of 24%, which is comparable to mortality rates for severe TBI among children defined by GCS or AIS scores in contemporary case series and prospective trials. 2,9,11,17,24,25,34,35,39,40,43,44,46,47 Nevertheless, the rate of neurosurgical procedures in the current study group (46.8%) was unexpectedly low. Even among admissions lasting 2 days or longer and ending in death, the rate of neurosurgical procedures was only 67.3%.…”
Section: The Missing Icp Monitorsmentioning
confidence: 76%
“…The current study confirmed the remarkably high mortality rate for admissions designated "self-pay," and this adverse effect of disadvantaged individual economic status persisted after lumping the category with Medicaid. 3,6,20,36,46 The association of higher mortality rates for trauma in the uninsured has been observed among adults as well. 3,18,42 The current study highlights the importance of community economic status, as reflected in the median income of home ZIP code.…”
Section: Mortality Ratesmentioning
confidence: 92%
See 2 more Smart Citations
“…45,46,55,56 Absence of insurance coverage, so-called "self-pay" status, is a particularly adverse factor. 24,43,55,56 In the pediatric age range, however, trauma patients admitted without insurance often acquire retroactive Medicaid coverage, and this coverage is registered in discharge data if the hospital stay is long enough. Patients with no insurance who die of their injuries tend to have relatively short lengths of stay in the hospital and may fail to acquire Medicaid coverage before discharge data are registered.…”
Section: Discussionmentioning
confidence: 99%